Analysis of Nitrogen Concentration and Distribution in Galesong Waters, Takalar Regency, South Sulawesi. - Nur Halizah Roebetho; Putri Sakinah Resman; Rahmat Pratama Putra; Andi Alya Yusriyyah; Amanda Pricella Putri; Asmi Citra Malina; Nita Rukminasari; Joeharnani Tresnati; Jamaluddin Fitrah Alam (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro, 2026)
This study evaluated the suitability of dissolved inorganic nitrogen relative to marine water quality standards, described horizontal distribution patterns, and examined links with non nutrient physicochemical parameters in the coastal waters of Galesong, Takalar. Sampling in April to May 2025 covered five stations representing nearshore, seaweed farming areas, and more open waters. In situ measurements included temperature, pH, dissolved oxygen, and salinity, and laboratory analyses quantified ammonium and nitrate with a spectrophotometer. Environmental conditions were within ranges favorable for seaweed growth. Ammonium was not detected at any station, while nitrate ranged from 0.017 to 0.023 mg L⁻¹, below the Government Regulation No. 22 of 2021 threshold of 0.06 mg L⁻¹. Spatial mapping showed higher nitrate concentrations at non farming stations, while the lower concentrations within farming areas indicate nitrogen uptake by cultivated seaweeds. Theese findings suggest that Galesong Waters remain suitable for seaweed aquaculture, provide that nutrient conditions are monitored regularly to prevent potential nutrient deficits that could reduce cultivation productivity.